A de novo Mutation in the MTUS1 Gene Decreases the Risk of Non-compaction of Ventricular Myocardium via the Rac1/Cdc42 Pathway - Bai, Xuehan; Zhou, Yuanlin; Ouyang, Na; Liu, Lingjuan; Huang, Xupei; Tian, Jie; Lv, Tiewei (Frontiers in Pediatrics, 2019)
Background: The MTUS1 gene encodes a microtubule-associated protein involved in multiple processes, including cell polarity and microtubule balance, during myocardial development. Aims: To investigate the association between a de novo c. 2617A->C mutation in MTUS1 (NM_001001924.2) and noncompaction of ventricular myocardium (NVM) and explore the potential mechanisms. Methods: A de novo mutation in MTUS1 was identified for a familial pedigree with NVM. Lentiviral vectors containing MTUS1 wild type and containing the mutation MTUS1 were constructed and co-infected into HEK-293 cells. MTUS1, Rac1/Cdc42, α-tubulin, α/β-tubulin, polarity protein (PAR6) and the morphology of daughter cells were measured by real-time PCR, Western blotting and immunofluorescence assays. Results: The lentiviral vectors were constructed successfully. Immunofluorescence assays revealed the fluorescence intensity of α-tubulin to be decreased and α/β–tubulin to be increased in the mutation MTUS1 group. The fluorescence intensity of PAR6 was higher and morphology of the daughter cells in the mutation group different from the wild type group. Phosphorylation of Rac1/Cdc42 in the mutation group was significantly lower than in the wild type group. Conclusions: A de novo mutation in MTUS1 decreased the stability of microtubules and increased cell polarity via the Rac1/Cdc42 pathway, which may partly elucidate the mechanism underlying cellular protection in NVM.